Chitosan gold nanoparticles induce cell death in HeLa and MCF-7 cells through reactive oxygen species production - Martínez Torres, Ana Carolina; Zárate Triviño, Diana Ginette; Lorenzo Anota, Helen Yarimet; Avila Ávila, Andrea; Rodríguez Abrego, Carolina; Rodríguez Padilla, María Cristina (Dove Medical Press, 2018)
Background: Nanotechnology has gained important interest, especially in the development of new therapies; the application of gold nanoparticles (AuNPs) in the treatment and detection of diseases is a growing trend in this field. As cancer represents a serious health problem around the world, AuNPs are studied as potential drugs or drug carriers for anticancer agents. Recent studies show that AuNPs stabilized with chitosan (CH) possess interesting biological activities, including potential antitumor effects that could be selective to cancer cells. Materials and methods: In this study, we synthesized sodium citrate-AuNPs and CHcapped AuNPs of 3–10 nm, and analyzed their cytotoxicity in cervical (HeLa) and breast (MCF-7) cancer cells, and in peripheral blood mononuclear cells (PBMCs). Then, we evaluated the clonogenic potential, cell cycle, nuclear alterations, caspase dependence, and reactive oxygen species (ROS) production in HeLa and MCF-7 cells after chitosan gold nanoparticles (CH-AuNPs) exposure. Results: Our data showed that CH-AuNPs are cytotoxic in a dose-dependent manner in the cancer cell lines tested, while they induce low cytotoxicity in PBMCs. Sodium citrate gold nanoparticles did not show cytotoxic effects. In both HeLa and MCF-7 cell lines, CH-AuNPs inhibit clonogenic potential without inducing cell cycle arrest or nuclear alterations. The cell death mechanism is specific for the type of cancer cell line tested, as it depends on caspase activation in HeLa cells, whereas it is caspase independent in MCF-7 cells. In all cases, ROS production is mandatory for cell death induction by CH-AuNPs, as ROS inhibition with N-acetyl cysteine inhibits cell death. Conclusion: Our results show that CH-AuNPs are selective for HeLa and MCF-7 cancer cells, rather than normal PBMCs, and that ROS production seems to be a conserved feature of the cell death mechanism induced by CH-AuNPs. These results improve the knowledge of CH-AuNPs and open the way to the design of new pharmacological strategies using these agents against cancer. Keywords: AuNPs, cancer, PBMC, nuclear alterations, cell cycle, ROS